Extension of Utaut's Theory on Central Java, Indonesia’s Acceptance of Tax E-Filling Applications - Airawaty, Diana; As'ari, Hasim; Wafa, Zaenal (Sean Institute, 2025)
This study investigates the utilization of computer programs for online tax filing among individual taxpayers in Central Java. This study surveyed taxpayers in the region by using the Purposive Sampling Method and extending the Unified Technology Acceptance and Application Theory (UTAUT). Findings reveal significant effects of performance expectancy and social influence factors on effort expectancy and behavioral intention to accept tax e-filing. However, this study did not establish empirical support for the impact of social influence and effort expectancy on behavioral intention. The novelty of extending the UTAUT framework contributes to advancing theory development in information systems research. This study contributes to understanding the adoption and acceptance of technological innovations, particularly in the context of tax e-filing practices in Central Java, explaining the factors that influence user behavior and acceptance levels.